I Was Ill and You Cared for Me : Biblical Reflections on Serving the Physically and Mentally Impaired - Craghan, John F. (Book collections on Project MUSE., 2014)
In I Was Ill and You Cared for Me, John F. Craghan offers readers a variety of biblical reflections to help family members, friends, and health care workers deal with the diminished physical and mental conditions of those they love and serve. These reflections will help these relationships become more meaningful, enriching, and helpful for all involved. They will also serve as an engaging invitation to further biblical study.